Decoding the Environmental Synergy in BRI Nations: Analyzing the Influence of Renewable Energy Adoption, Financial Evolution, FDI, and Capital Resilience on Sustainability - Sylvia Kor; Md. Qamruzzaman (International Journal of Energy Economics and Policy)
In response to escalating global concerns over environmental degradation, this study explores the intricate relationships between financial development (FD), foreign direct investment (FDI), capital adequacy, renewable energy consumption (REC) and environmental sustainability in BRI. We aim to provide nuanced insights into how these economic variables impact environmental quality, contributing to a comprehensive understanding of the complex interplay between economic development and environmental conservation. We aim to explore the associations between FD, FDI, REC, and capital adequacy, and environmental quality, emphasizing short-term and long-term dynamics. We employ the Autoregressive Distributed Lag (ARDL) model and conduct D-H causality tests to discern these variables' temporal and causal relationships. This methodology allows us to capture the complexities of the relationships and provide a robust analysis of their impacts on environmental sustainability. The findings reveal a positive long-run association between FD and environmental quality, suggesting that a well-developed financial sector may contribute positively to environmental outcomes. However, the short-run dynamics introduce complexity, indicating a potential immediate positive impact and raising questions about contextual factors influencing FD's contribution to increased carbon emissions. Shifting the focus to FDI and REC, our research uncovers a potential positive association with environmental quality in the long run. The short-run analysis introduces nuances, suggesting a potential negative impact, reflecting the mixed effects observed in previous studies, which underscores the importance of considering temporal dimensions and policy interventions to enhance the positive contributions of FDI and REC to environmental sustainability. Further, our study delves into the impact of capital adequacy on environmental sustainability, revealing a positive long-run association, which challenges negative associations, underlining the need for tailored policies to balance economic growth and environmental conservation. As a whole, our findings contribute quantitative evidence to guide policymakers in fostering incremental improvements over time, acknowledging the multifaceted nature of the relationships under consideration.